Redescription of P. dorsipapillatus (von Marenzeller, 1893) and additional comments on the other species in the genus Pholoides Pruvot, 1895 (Polychaeta: Sigalionidae) - Hintze, Katharina; Meißner, Karin; Bick, Andreas (Zootaxa, 2018)
Pholoides Pruvot, 1895 is a species-poor genus of small scale-bearing polychaetes. Pholoides species are restricted to the continental shelf, living in sandy and muddy substrates, or on hard bottoms. During the DIVA 3 expedition grab samples were taken on four seamounts of the Meteor Seamount complex. One of the most common polychaetes in these samples was P. dorsipapillatus (von Marenzeller, 1893). Based on this material a comparison with the type material is undertaken leading to a re-description of P. dorsipapillatus. Diagnostic characters of all accepted Pholoides species were evaluated using light, scanning electron and confocal laser scanning microscopy. CLSM in particular proved to be an excellent tool for investigating these small species, and especially the type material. Blossom-like sensory buds, found at certain appendages of P. dorsipapillatus, could be an important diagnostic character to distinguish P. dorsipapillatus from other Pholoides species. Sequence information on three different gene fragments, the mitochondrial COI and 16S and the nuclear H3a, were obtained, and could serve for future phylogenetic and phylogeographic studies.